USE OF HELIOS AIR HEATERS FOR PRE-DEHUMIDIFICATION OF WALNUTS - TSURKAN, OLEH; SPIRIN, ANATOLII; RUTKEVYCH, VOLODYMYR; DIDYK, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The issue of reducing energy costs in the technological process of post-harvest processing of walnuts by using solar air heaters is considered. It is noted that preliminary dehumidification of walnuts before drying is a key stage in post-harvest processing of walnuts, which ensures the preservation of product quality, reduction of energy costs and extension of storage life. The advantages, technical features and feasibility of using solar air heaters operating on the basis of solar energy are considered. It is noted that a significant reduction in energy consumption (up to 50%), environmental safety, preservation of the natural texture and color of the kernel, uniformity of the dehumidification process and optimization of subsequent drying open up wide opportunities for increasing energy efficiency in agriculture. And the integration of solar heaters with alternative energy source systems, the introduction of automation and adaptation to different climatic conditions make this technology an innovative solution for the sustainable development of the agro-industrial complex. A structural and technological scheme of a conveyor for transporting walnuts from the peeling department to a convective-vibration dryer with simultaneous removal of surface moisture from wet nuts is proposed. An innovative approach to solving the problem of preliminary dehumidification of nuts consists in supplying air from above to the wet nuts being transported, as well as simultaneous heating of the air used to remove surface moisture. The prospects of using solar heaters to improve product quality and promote greening of production, which corresponds to modern trends in the agricultural sector, are indicated.